Financial Structure and Firm Innovation Evidence from around the World - Mare, Davide S. (The World Bank, 2021)
This paper analyzes the relationship between financial structure and innovation. Analysis of cross-country micro data over 2009-18 shows that a firm's financial sources matter for the choice to innovate and the extent to which a firm innovates. The relationship is stronger for firms relying on non-bank financial intermediaries and for firms in low-technology sectors. Moreover, the use of external sources of finance is associated with improved prospects of innovation, especially in more financially developed countries. These findings suggest that developing the financial sector can bring benefits in terms of innovation